Here's the question you clicked on:
AGummiBear55
PLEASE HELP me solve the inequality: –2(x – 3) ≥ 5 – (x + 3) Here's my work so far: -2(x-3)>=5-(x-3) -2x+6>=5-5x+15 -2x+6>=5x-10 -6 on both sides -2x>=5x-16 -5x on both sides -7x>=-16 -7x on both sides That's what I'm doing but it isn't getting the right answer , I think! HELP!
–2(x – 3) ≥ 5 – (x + 3) -2x + 6 ≥ 5 - x - 3 -2x + 6 ≥ 5 - 3 - x -2x + 6 ≥ 2 - x 6 - 2 ≥ 2x - x 4 ≥ x
... wait... how did you get -2x + 6 ≥ 5 - x - 3 ??
Yeah, but don't you distribute 5 to x for 5x and then 5 to 3 to get 15?!?
No bro. Don't you see that my solution is correct?
Yeah, I do... guess I'm still a little confused though...
The 5 is not being multiplied with the (x+3); it is 5 + -1(x+3) which gives 5 - x - 3
ahh... I got it now... thanks you guys!!! :D